2015
DOI: 10.1093/ejcts/ezv321
|View full text |Cite
|
Sign up to set email alerts
|

Transition from a multiport technique to a single-port technique for lung cancer surgery: is lymph node dissection inferior using the single-port technique?

Abstract: The total number of dissected lymph nodes for primary lung cancer surgery by single-port video-assisted thoracoscopic surgery (VATS) was higher than by multiport VATS in univariable, multivariable linear regression and Box-Cox transformed multivariable analyses. This study confirmed that highly effective lymph node dissection could be achieved through single-port VATS in our setting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
63
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(68 citation statements)
references
References 17 publications
4
63
0
1
Order By: Relevance
“…After removing duplicates, irrelevant articles, case reports, letters, reviews, comments or meta-analyses, 15 references were identified and assessed further by screening the full texts. After the exclusion of four studies which did not provide the appropriate data, 11 studies (2)(3)(4)(5)7,8,(12)(13)(14)(15)(16) were included for final assessment and were deemed to be suitable for quantitative meta-analysis. The process of article selection is summarized in Figure 1.…”
Section: Selection Processmentioning
confidence: 99%
“…After removing duplicates, irrelevant articles, case reports, letters, reviews, comments or meta-analyses, 15 references were identified and assessed further by screening the full texts. After the exclusion of four studies which did not provide the appropriate data, 11 studies (2)(3)(4)(5)7,8,(12)(13)(14)(15)(16) were included for final assessment and were deemed to be suitable for quantitative meta-analysis. The process of article selection is summarized in Figure 1.…”
Section: Selection Processmentioning
confidence: 99%
“…To date, results comparing number and station of lymph nodes between SP VATS and MP VATS have been discordant (15,17,19). Our data showed that the number of lymph nodes harvested by SP VATS was not different from MP VATS.…”
Section: Discussionmentioning
confidence: 61%
“…Delgado et al (48) reported better results in uniVATS than in multiport VATS for mediastinal lymphadenectomy. More recently, Liu et al (49) observed that the quantity and quality of dissected lymph nodes was similar, whatever the used VATS approach.…”
Section: The Recent Progressmentioning
confidence: 95%